The second mountain [large type] : the quest for a moral life - Brooks, David, 1961- (Random House Large Print, 2019)
Every so often, you meet people who radiate joy<U+2014>who seem to know why they were put on this earth, who glow with a kind of inner light. Life, for these people, has often followed what we might think of as a two-mountain shape. They get out of school, they start a career, and they begin climbing the mountain they thought they were meant to climb. Their goals on this first mountain are the ones our culture endorses: to be a success, to make your mark, to experience personal happiness. But when they get to the top of that mountain, something happens. They look around and find the view . . . unsatisfying. They realize: This wasn<U+2019>t my mountain after all. There<U+2019>s another, bigger mountain out there that is actually my mountain. And so they embark on a new journey. On the second mountain, life moves from self-centered to other-centered. They want the things that are truly worth wanting, not the things other people tell them to want. They embrace a life of interdependence, not independence. They surrender to a life of commitment. In The Second Mountain, David Brooks explores the four commitments that define a life of meaning and purpose: to a spouse and family, to a vocation, to a philosophy or faith, and to a community. Our personal fulfillment depends on how well we choose and execute these commitments. Brooks looks at a range of people who have lived joyous, committed lives, and who have embraced the necessity and beauty of dependence. He gathers their wisdom on how to choose a partner, how to pick a vocation, how to live out a philosophy, and how we can begin to integrate our commitments into one overriding purpose.